A compact UWB‐MIMO with dual grounded CRR for isolation improvement. Issue 1 (10th November 2018) - Mathur, Rohit; Dwari, Santanu
Abstract: In this article, a compact half‐hexagonal ultra‐wide band multiple‐input‐multiple‐output (MIMO) antenna is presented. The key feature of the antenna is its novel isolation improvement technique which includes grounded stub along with dual grounded circular ring resonator. The antenna contains two counter facing half‐hexagonal monopoles having hybrid isolation circuit. The antenna has a compact size of 20 × 34 mm 2, with operating frequency band of 3‐11 GHz where port isolation is better than 20 dB in most of the band. The MIMO performance is ensured by calculating envelop correlation coefficient and mean effective gain ratio for isotropic, indoor, and outdoor environment. The performance of the antenna with multilayer printed circuit board having large dual ground plane and device housing is also studied. Results show that the proposed MIMO antenna is a good candidate for handheld devices for wireless personal‐area networks application.